1985
DOI: 10.1136/hrt.53.3.314
|View full text |Cite
|
Sign up to set email alerts
|

Pre-excitation due to accessory sinoventricular connexions associated with coronary sinus aneurysms. A report of two cases.

Abstract: Ventricular pre-excitation occurred in two cases in which the accessory pathways between the atria and the ventricles were histologically identified as being associated with aneurysmal malformations of the coronary sinus. In one case the connexions were in the posterior wall of the coronary sinus aneurysm and were not related to the atrioventricular annulus; in the other, a connexion was situated in the anterior wall of the aneurysm in close apposition to the annulus and superficially resembled a Kent fibre. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…When the CS progresses into an intimate anatomical relation with the ventricles, it remains possible that extensions of the sinus venosus muscle could be responsible for a physiological connection. 20) Not only CS abnormalities, but also CS dilatation, as shown in the present study, could occur during this development.…”
Section: Cs Diameter and Morphologysupporting
confidence: 72%
“…When the CS progresses into an intimate anatomical relation with the ventricles, it remains possible that extensions of the sinus venosus muscle could be responsible for a physiological connection. 20) Not only CS abnormalities, but also CS dilatation, as shown in the present study, could occur during this development.…”
Section: Cs Diameter and Morphologysupporting
confidence: 72%
“…The generation of some atrial arrhythmias may relate to the spiral sheath of myocardium surrounding the CS and its connections to the right and left atria. The muscle sheath may represent a remnant of the sinus venosus (Gerlis et al, 1985). In electrophysiological studies performed in canine hearts, Antz et al showed that the CS musculature is electrically connected to the right and left atrium.…”
Section: Discussionmentioning
confidence: 99%
“…C oronary sinus (CS) diverticula [1][2][3][4][5] have been associated with posteroseptal and left posterior accessory pathways. These diverticula contain myocardial fibers that connect to both the ventricle and the CS myocardial coat.…”
mentioning
confidence: 99%
“…These diverticula contain myocardial fibers that connect to both the ventricle and the CS myocardial coat. 1,2 The CS myocardial coat, present in all individuals, 6 is anatomically 6 -9 and electrically 10 connected to both atria, completing the accessory connection.…”
mentioning
confidence: 99%